P-17 Advance care planning in victoria – we have a plan!. (1st September 2015) - Doran, N; Austin-Crowe, Z
Abstract : Background: Victoria has developed and introduced Advance care planning: Have the conversation; A strategy for Victorian health services 2014–2018 . This strategy is accompanied by a comprehensive implementation plan which will be the subject of this poster. Aim: To maximise the outcomes of this strategy a multi pronged implementation plan supports implementation. It comprises a communication strategy, funded initiatives and monitoring and evaluation framework all of which are overseen by a strategy implementation advisory group. Methods: Evidence, and learnings from Victoria's experiences and outcomes in implementing advance care planning (ACP) have informed the development of the strategy and also the implementation plan that accompanies it. Implementation science is ensuring that the strategy objectives have broad support from all relevant stakeholders, have commitment at executive levels, are measurable, achievable and sustainable. Results: Victoria's Public Advocate chairs the implementation advisory group, which is guiding implementation over the four years. Funded initiatives are supporting the strategy goals. A communication strategy is targeting clinicians and consumers and a monitoring and evaluation framework tracks implementation progress. Discussion and conclusion: In recognition that ACP can only be successful and sustainable if all parts of the health service sector and community are engaged, funded initiatives are developing resources to: raise ACP awareness and support consumers to undertake ACP, including ethnic communities; build clinician confidence and competence; develop systems across providers – ambulance, general practitioners, community providers, hospitals and residential aged care. Reporting against the monitoring and evaluation framework will inform the success of this strategy.